Physicochemical and Sensory Characteristics of Cuko Pempek with The Addition of Organic Acid - Friska Syaiful; Tian Nabila Maharani; Merynda Indriyani Syafutri (Journal of Applied Food Technology, 2025)
Cuko pempek is the accompanying sauce when consuming pempek.  One of the ingredients used to make cuko is acid. This study aimed to see the effect of using several types of organic acids on the physicochemical and sensory characteristics of cuko. The analysis method used a Factorial Completely Randomized Design with two treatment factors, namely acid type (tamarind, kandis acid, key lime) and acid concentration (5% and 10%), Viscosity, pH, total acid, total soluble solids and hedonic test on taste and aroma were analyzed in this study. The results showed that the type of acid had a significant effect (α=0.05) on viscosity, pH, and total soluble solids.  Meanwhile, acid concentration significantly influenced pH, total acid, and total solids. Sensory test showed that acid type and acid concentration significantly influenced the flavor and aroma of cuko pempek. Based on sensory analysis, panelists preferred cuko with low concentration of tamarind and kandis acid added, namely 5% acid.